Grain growth and yield of whea under different irrigation regimes - Haider, SA; Alam, MZ; Paul, NK (Journal of Life and Earth Science, 2011)
A field experiment was carried out to study the influence of different irrigation regimes on the panicle and grain growth, relative growth rate of grain, grain abortion, yield and some yield components of four wheat varieties in two growing seasons. Irrigation regimes had significant effects on the aforesaid parameters and the varieties were found to be more efficient under well irrigated conditions. A drastic reduction in panicle and grain growth and yield and increase in grain abortion was noticed when the varieties were grown under rainfed condition. C 306 was found to be the most efficient to have higher values of panicle and grain growth, relative grain growth rate and yield under all the irrigation regimes in both the growing seasons. Key words: Wheat; irrigation; relative growth rate; grain abortion DOI: 10.3329/jles.v2i2.7495 J. Life Earth Sci., Vol. 2(2) 35-41, 2007